A Safety impact quantification approach for early stage innovative aviation concepts: Application to a third pilot adaptive automation concept - CAHILL, JOAN; Stroeve, Sybert H.; van Doorn, Bas A. (EU Commision, 2016)
This paper presents a straightforward approach for safety impact quantification of innovative aviation concepts in early development stages. The safety impact quantification approach provides a high-level and broad overview of the accident risk reduction that may be obtained by the novel concept. The approach uses a systematic assessment of change factors for base event probabilities in a total aviation system risk model, consisting of combinations of event sequence diagrams and fault trees. The approach is illustrated in terms of the assessment of an innovative third pilot adaptive automation concept. The results indicate that this concept can effectively reduce the fatal accident risk.
SESAR Innovation Days
Keywords: Accident risk; Adaptive automation; Safety; Smart & Sustainable Planet; Safety Quantification; Transport